PARADIGMA KEPEMIMPINAN DANIEL BAGI PELAYANAN PUBLIK KRISTEN KONTEMPORER - Manoach, Ronald Michael; Waani, Marciano Antaricksawan (Sekolah Tinggi Teologi Aletheia, 2026)
This study departs from the critical relevance of the life narrative of Daniel in the Book of Daniel as a paradigmatic expression of contextual leadership ethics for Christians involved in contemporary public service. In the present social milieu, Christians frequently face tensions between upholding the integrity of their faith and fulfilling responsibilities within a complex public sphere. The purpose of this research is to conduct a critical examination of the ethical values embodied in Daniel’s leadership and to evaluate their applicability for constructing a model of public leadership rooted in Christian faith. Through a qualitative approach employing textual analysis of the Book of Daniel, the study contributes to scholarship by formulating principles of Christian ethical leadership derived from Scripture and attuned to today’s socio-political realities. The findings not only reaffirm Daniel’s steadfast faith, moral integrity, and courage but also articulate a conceptual framework that may serve as a strategic reference for developing Christian leadership ethics in the modern public domain.